Studying structurally-mechanical characteristics suppositories with amlodipine - Zedan, Fadi Al; Gladyshev, V. V.; Burlaka, B. S. (Zaporozhye Medical Journal, 2013)
Rheological behaviour suppositories with amlodipine on lypofiles to a basis are studied and character of temperature effect on their structurally-mechanical properties is positioned. It is revealed that the temperature of carrying out of technological operations of homogenization and overflow suppositories 50-55ºС is optimum, providing necessary fluidity suppositories masses at hypodispersion in it reacting and aids.